Linking growth dynamics and intra-annual density fluctuations to late-summer precipitation in humid subtropical China - Wang, Chunsong; Zheng, Zhuangpeng; Gao, Jiani; Zhou, Feifei; Rossi, Sergio; Fang, Keyan (Frontiers in Plant Science, 2025)
Global warming has intensified extreme rainfall events and prolonged droughts, significantly impacting tree growth and wood formation. This study investigates the effects of late-summer precipitation variability on the intra-annual growth dynamics of Cunninghamia lanceolata and Cryptomeria fortunei in humid subtropical China. Microcores were collected from 12 trees at 7–10 days intervals between March and December from 2021 to 2023 in the Gushan Mountains. Typically, high temperatures and rainfall deficits in July induce cambial dormancy, while subsequent rainfall in August and September reactivates growth, resulting in a bimodal growth pattern. However, in 2022, an unprecedented drought (August–October rainfall 77% below average) shortened the growing season, causing an early cessation of growth and a rare unimodal growth pattern. In contrast, persistent rainfall in 2023 accelerated cell enlargement to 7 μm d-¹ and significantly increased latewood intra-annual density fluctuations (L-IADFs). Notably, despite abundant late-summer rainfall in 2021, L-IADFs did not form, indicating a nonlinear and inconsistent relationship between rainfall and L-IADFs. These findings highlight the critical role of late-summer precipitation variability in shaping tree growth patterns and wood density in southeastern China. Given the expected increase in precipitation variability under climate change, regional forest ecosystems may become more vulnerable. This study provides valuable insights for forest management strategies to enhance resilience and mitigate climate-related risks.